Circuits for the Charge Push-through Electronics: Power Efficient Signal Processing Inside the Artificial Cochlear Implant. (2016) - Zak, Jaromir; Hubalek, Jaromir; Prasek, Jan; Pekarek, Jan; Svatos, Vojtech; Hadas, Zdenek; Dusek, Daniel
Abstract: This work deals with the new technique called Charge Push-Through technology which is more energy efficient than the currently used approaches. The new energy efficient design regarding utilization of emerging technology such as Energy harvesting (EH) power sources is very promising for future development of energy independent (zero-power) and nonobtrusive cochlear implant. This work presents the solution of Charge Push-Through circuits using the component level design of artificial cochlea.